2017
DOI: 10.1515/adms-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of a Repair Weld in a Nickel Based Superalloy Gas Turbine Component

Abstract: The aim of the present study was to characterize the repair weld of serviced (aged) solid-solution Ni-Cr-Fe-Mo alloy: Hastelloy X. The repair welding of a gas turbine part was carried out using Gas Tungsten Arc Welding (GTAW), the same process as for new parts. Light microscopy, scanning electron microscopy, transmission electron microscopy, microhardness measurements were the techniques used to determine the post repair condition of the alloy. Compared to the solution state, an increased amount of M 6 C carbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…19,No. 2 (60), June 2019 in structural steels [2] and in advanced micro-alloyed steels and alloys for high-temperature and high-pressure applications [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…19,No. 2 (60), June 2019 in structural steels [2] and in advanced micro-alloyed steels and alloys for high-temperature and high-pressure applications [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation was also reported on Alloy X by another investigator. 38 Sihotang et al 39 reported that the P precipitate is observed around the M 6 C phases. The absence of microsegregation in the GTA and PCGTA Figure 8.…”
Section: Sem/eds Observationmentioning
confidence: 99%
“…The factor that can successfully mitigate the effects of such crises is the continuous improvement of power unit efficiency. This has prompted the power sector to increase the pressure and temperature of their steam boilers to reduce CO 2 , NO x , and SO x emissions [1][2][3][4]. Due to environmental restrictions having increased in recent years, new advanced ultra-supercritical (A-USC) plants ensure presently higher efficiencies compared to conventional fossil-burning power investigate the influence of the various Al/Ti ratios and tantalum addition on the primary microstructure, microsegregation of alloying elements, phase transformation temperatures, coefficient of thermal expansion and Vickers hardness.…”
Section: Introductionmentioning
confidence: 99%